Pengaruh kemampuan kerja dan dukungan organisasi terhadap kinerja karyawan yang di mediasi oleh motivasi berprestasi pada PT. Dimensi Ruang Digital di Yogyakarta - Novrilisma Perdana, Muhammad Rizki; Mustafa EQ, Zainal (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Awareness of the fast development of the times must be understood by business people, because this is important related to the changing times that are changing to the digital era. This study aims to examine the effect of work ability and organizational support on employee performance which is mediated by achievement motivation. The research method used is a quantitative method, with 62 respondents taking samples using the census method because the number of respondents is below 100 people, all populations are used as samples. The results showed that work ability has a significant effect on achievement motivation, organizational support has a significant effect on motivation, work ability has no effect on employee performance, organizational support has no effect on employee performance, achievement motivation has a significant effect on employee performance, achievement motivation mediates the effect of work ability on employee performance, and achievement motivation mediate the effect of organizational support on employee performance.